2017
DOI: 10.1016/j.jsps.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between health literacy and body mass index among Arab women with polycystic ovary syndrome

Abstract: Improving the health literacy of patients with PCOS may have a positive impact on their BMI and eventually lead to favorable health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 26 publications
2
24
0
1
Order By: Relevance
“…After controlling for confounding factors such as age, education etc., PCOS patients with higher BMI were almost 10% less likely to have good HL compared to others with lower BMI. The limitations of this study were the use of only one HL item and that the results cannot be generalized due to the study design (18).…”
Section: Studies In Adultsmentioning
confidence: 96%
See 1 more Smart Citation
“…After controlling for confounding factors such as age, education etc., PCOS patients with higher BMI were almost 10% less likely to have good HL compared to others with lower BMI. The limitations of this study were the use of only one HL item and that the results cannot be generalized due to the study design (18).…”
Section: Studies In Adultsmentioning
confidence: 96%
“…In 17 out of 22 studies reviewed, low HL was significantly associated with increased body mass index, overweight and obesity (4,5,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). However, quite a few studies failed to support the above finding.…”
Section: Low Health Literacy and Excess Body Weightmentioning
confidence: 98%
“…Results of this novel study showed that PCOS women are suffering from low QOL and that could be related to the worst symptoms of this syndrome that is the infertility. Previous reports have shown that a high percentage (69.8%) of women with PCOS have no children . In this study, the percentage of participants who reported not to have children was also high 44.4% (excluding unmarried women).…”
Section: Discusionmentioning
confidence: 61%
“…In addition, the Arabic-GASS was not validated against any valid scale in Arabic mainly due to the lack of any validated self-report antipsychotic side effects scale in Arabic. Moreover, this study highlighted on the importance of health literacy in reporting drug side effects among psychiatric patients, however, the used tool was not as reliable as other health literacy screening tools such as the Rapid Estimate of Adult Literacy in Medicine and the Short Test of Functional Health Literacy in Adults [ 48 50 ]. Despite these potential imperfections, it is expected that the Arabic-GASS will improve treatment outcomes for Arabic-speaking psychiatric patients by helping them to express their concerns about the side effects of antipsychotic medications.…”
Section: Discussionmentioning
confidence: 99%
“…The Charlson comorbidity index (CCI) was used to measure comorbidities [ 47 ]. Health literacy was assessed using the Arabic version of the Single Item Literacy Screener (SILS) [ 48 50 ]. This tool consists of a single question that assesses the respondent’s ability to read and comprehend educational information and instructions about different medical conditions and medications without anyone’s help [ 48 ].…”
Section: Methodsmentioning
confidence: 99%